Nanotechnology Applications in the Single-Cell Analysis for Cancer and Therapy - Ali Hamad Abd Kelkawi (Journal of Global Pharma Technology, 2019)
Understanding the molecular, cell, genetic, and functional heterogeneity of tumors at the cell level has become a major challenge to cancer research. Microfluidic technology has emerged as an important tool that offers advantages in single-cell analysis with the ability to integrate labor-intensive, labor-intensive experimental procedures, such as single-cell capture into a single small device at ease and in high productivity. Single-cell processing and analysis can be performed within a microfluidic multifunctional device for various applications in cancer research. Here, we present recent developments in microfluidic devices for single-cell analysis related to cancer biology, diagnosis, and treatment. First, we briefly present several microfluidic pads used to analyze one cell, followed by different microfluidic techniques to manipulate a single cell. Next, we highlight their various applications in cancer research, with a focus on cancer biology, diagnosis, and treatment. Current limitations and potential trends of one microfluidic cell analysis are discussed in the end.Keywords: Microfluidic lab-on-a-chip, Single cell analysis, Cancer biology, Cancer diagnosis, Cancer therapy, Cancer research.